A case series of paediatric atrial myxoma: Clinical challenges and surgical management: Atrial Myxoma - Septyandra, Ezi; Bermansyah; Nugraha, Aswin; Nova, Ria (Journal of Indonesia Vascular Access, 2024)
Introduction : Cardiac myxomas are rare, benign tumors of the heart, most commonly found in the left atrium, though they can occur in any heart chamber. These tumors can embolize, causing organ infarction, and may present with symptoms such as dyspnea, orthopnea, cough, peripheral edema, palpitations, and fatigue. The clinical presentation varies widely and may mimic other diseases, making early detection and diagnosis critical. The reported incidence of cardiac myxoma at RS Mohammad Hoesin is 5 cases over 2023-2024, consisting of 3 pediatric cases and 2 adult cases. This report emphasizes the significance of thorough history taking, detailed physical examination, echocardiography, and surgical resection in managing atrial myxoma in two paediatric patients. Case Presentation : We reported three cases: a 16-year-old male, an 11-year-old female, and 12-year-old male, They were presenting with shortness of breath as the chief complaint. The male patient was diagnosed with decompensated heart failure due to a large left atrial myxoma, accompanied by tricuspid and pulmonary regurgitation, and underwent successful surgical removal of the myxoma. The female patient, with a history of contact with tuberculosis, was found to have a mass in the right atrium with a differential diagnosis of myxoma or tuberculoma. She was treated for clinical pulmonary tuberculosis and is currently under medical management. The last patient, male was diagnosed with a large left atrial myxoma, tricuspid regurgitation, and severe mitral regurgitation. The myxoma had removed from the left atrium in this patient. Conclusion : Paediatric atrial myxoma is a rare condition with a wide range of clinical manifestations, from asymptomatic cases to intracardiac obstruction, embolization, and constitutional symptoms. This often results in misdiagnosis as other more common heart diseases. Transthoracic echocardiography is useful as an initial diagnostic tool, as it effectively determines the tumor's location, size, shape, and connections, aiding in the selection of the optimal management strategy. Surgical excision is the primary treatment, with regular echocardiographic follow-up essential for the early detection of recurrence and long-term patient health.